Selected Phrasemes in Slovenian and Their (Non-)Systemic Equivalents in Croatian - Ulčnik, Natalija (Slavistična prepletanja 6, 2025)
This paper examines selected examples of Slovenian phrasemes from the FRIDA phraseological collection in the "Slovenian in the Palm of Your Hand" e-learning environment, focusing on the search for their (non-)systemic equivalents in Croatian using a corpus-based approach. The emphasis is on phraseological units for which it was particularly challenging to find systemic equivalents in Croatian online lexicographic sources, such as dictionaries and phraseological databases. To address this issue, we also utilized a parallel corpus search with the Sketch Engine tool, specifically examining the OpenSubtitles 2018 parallel – Slovenian. Our goal was to explore translation possibilities and identify potential systemic (phraseological) equivalents that may have been previously overlooked. Additionally, we evaluated the topicality and relevance of Croatian equivalents that had been identified earlier.